2015
DOI: 10.3390/s150923168
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Smartphone Inertial Sensors Measurement for Range of Motion

Abstract: Over the years, smartphones have become tools for scientific and clinical research. They can, for instance, be used to assess range of motion and joint angle measurement. In this paper, our aim was to determine if smartphones are reliable and accurate enough for clinical motion research. This work proposes an evaluation of different smartphone sensors performance and different manufacturer algorithm performances with the comparison to the gold standard, an industrial robotic arm with an actual standard use ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 24 publications
2
73
0
Order By: Relevance
“…The filter has been improved recently in [7], employing the accelerometer and magnetometer measurements in a gradient descent algorithm to correct the quaternion obtained through the integration of rate measurements. Mahony and Madgwick filters are widely utilized algorithms and their performances have regularly been considered in comparative Sensors 2020, 20, 803 3 of 29 analyses [9,13,15,[31][32][33]. In [34], an adaptive-gain CF was proposed to provide good estimates, even in dynamic or high-frequency situations.…”
mentioning
confidence: 99%
“…The filter has been improved recently in [7], employing the accelerometer and magnetometer measurements in a gradient descent algorithm to correct the quaternion obtained through the integration of rate measurements. Mahony and Madgwick filters are widely utilized algorithms and their performances have regularly been considered in comparative Sensors 2020, 20, 803 3 of 29 analyses [9,13,15,[31][32][33]. In [34], an adaptive-gain CF was proposed to provide good estimates, even in dynamic or high-frequency situations.…”
mentioning
confidence: 99%
“…This, on the one hand, reduces costs, and on the other, eliminates the problem of having to learn how to use a new device. Moreover, studies demonstrated that samples from smartphones sensors (e.g., accelerometer and gyroscope) are accurate enough to be used in clinical domain, such as ADLs recognition [22]. This is also confirmed by the amount of publications that rely on the use of smartphones as acquisition devices for fall detection systems [18,23] and ADLs recognition.…”
Section: Introductionmentioning
confidence: 69%
“…It was chosen because of its convenience and location, as discussed earlier. However, it has been shown that sensors included in current smartphones are equally accurate as consumer wearables [45]. In that sense, one could replace the SenseWear with, e.g., a smartphone mounted in a typical sports armband used by runners.…”
Section: Discussionmentioning
confidence: 99%